Historical Costume as Part of the Ethnogenesis of Cultural Ties and Aesthetic Ideals of the Sarmatians - S. Kainbayeva, Zhamila; N. Sdykov, Murat; V. Pak, Yuliya (International Journal of Psychosocial Rehabilitation, 2020)
The work deals with the secondary reconstruction of the historical costume "Altyn khanshaiym," or the "Golden Princess," found in 2012 by archaeologists of the West Kazakhstan regional center of history and archaeology (Uralsk, Kazakhstan). The primary reconstruction of the costume was done by the famous restorer Krym Altynbekov and specialists of the cientific restoration laboratory "Ostrov Krym" (Almaty, Kazakhstan). They have developed a version of the artistic reconstruction of the female image based on the materials from mound 6 of the Taksay-1 complex (village Dolinnoe, West Kazakhstan region, Kazakhstan). However, this image of the historical costume cannot be considered final. There are disputes on the materials, color gamut, elements of the Golden Princess's suit, her dress, kaftan, and a headdress. The work analyzes archaeological materials and historical literature about the Sarmatians costume, as well as presents a scientifically grounded view of artists and designers of the West Kazakhstan State University named after M. Utemisov (Uralsk, Kazakhstan) on the historical costume of the Golden Princess as part of the ethnogenesis of cultural ties and aesthetic ideals of the Sarmatians.